Ensino da leitura no método intuitivo: as palavras como unidade de compreensão e sentido - Valdemarin, Vera Teresa [UNESP] (Setor de Educação da Universidade Federal do Paraná, 2001)
This article presents results of research about the objective methods, by Norman A. Calkins, especially to teaching reading method. For the author, the words are the units trough the teaching should happen, relating it to the propositions of analytic methods that appeared in the 19th Century, innovating the procedures of general teaching.

Este artigo apresenta resultados de pesquisa sobre o método de ensino intuitivo, elaborado por Norman A. Calkins, especialmente para o ensino da leitura. Para o autor, as palavras são as unidades a partir das quais o ensino deve se dar, filiando-se às proposições de marcha analítica que surgem no século XIX, inovando os procedimentos de ensino.
Teaching reading by objective method: the words as units of understanding and sense
Keywords: Objective methods; Teaching reading; Objective lessons; 19th century education; Método intuitivo; Ensino de leitura; Lições de coisas; Educação no século XIX